Handover Parameter for Self-optimisation in 6g Mobile Networks: A Survey - Ukasyah Mahamod; Ibraheem Shayea; Hafizal Mohamad; Marinah Othman; Fauzun Abdullah Asuhaimi (Elsevier, 2024)
Indexed by WOS/Scopus/ERA